Influence of Brand Awareness and Brand Image on Purchase Decision of Indihome Services at PT Telkom Indonesia Regional IV Jateng-DIY - Farouk, Umar -; Jumi, Jumi -; S, Natasya Annisa (Admisi dan Bisnis, 2023)
This study was used to examine the effect of Brand Awareness (X1) and Brand Image (X2) on Purchasing Decisions (Y) of PT Telkom Indonesia IndiHome services Regional IV Jateng DIY. This research is based on declining sales and decreasing consumer perceptions of IndiHome services in 2022. The objects in this study are IndiHome service customers in Semarang City, with data on the number of sales of IndiHome services in 2022 obtained as many as 44,092 sales. The number of samples taken to conduct the research was 100 respondents using a purposive sampling technique. This research is a type of quantitative research using literature and questionnaires as research data collection tools. The questionnaire uses a Likert scale as a measurement scale in research. The analysis model used in this study is a multiple linear regression analysis model. Data calculations were carried out in the survey using the SPSS application. Based on the calculation results, brand awareness, and brand image significantly and positively influence the purchasing decisions of IndiHome service customers.